Striatal dopamine type 2 receptor availability in anorexia nervosa. Issue 3 (30th September 2015) - Broft, Allegra; Slifstein, Mark; Osborne, Joseph; Kothari, Paresh; Morim, Simon; Shingleton, Rebecca; Kenney, Lindsay; Vallabhajosula, Shankar; Attia, Evelyn; Martinez, Diana; Timothy Walsh, B.
Abstract: The neurobiology of anorexia nervosa remains incompletely understood. Here we utilized PET imaging with the radiotracer [ 11 C]raclopride to measure striatal dopamine type 2 (D2 ) receptor availability in patients with anorexia nervosa. 25 women with anorexia nervosa who were receiving treatment in an inpatient program participated, as well as 25 control subjects. Patients were scanned up to two times with the PET tracer [ 11 C]raclopride: once while underweight, and once upon weight restoration. Control subjects underwent one PET scan. In the primary analyses, there were no significant differences between underweight patients ( n =21) and control subjects ( n =25) in striatal D2 receptor binding potential. Analysis of subregions (sensorimotor striatum, associative striatum, limbic striatum) did not reveal differences between groups. In patients completing both scans ( n =15), there were no detectable changes in striatal D2 receptor binding potential after weight restoration. In this sample, there were no differences in striatal D2 receptor binding potential between patients with anorexia nervosa and control subjects. Weight restoration was not associated with a change in striatal D2 receptor binding. These findings suggest that disturbances in reward processing in this disorder are not attributable to abnormal D2 receptor characteristics, and that other reward-related neural targets may be of greater relevance. Highlights: This study measured striatal D2 receptor availability in anorexia nervosa using PET. Patients were scanned while underweight, and after nutritional restoration. No differences in D2 availability between patients and controls subjects were seen. Striatal D2 receptor availability was not associated with clinical measures.